Immunomodulation in the Treatment of Periodontitis: Progress and Perspectives - Yang, Bo; Pang, Xuefei; Li, Zhipeng; Chen, Zhuofan; Wang, Yan (Frontiers in Immunology, 2021)
Periodontitis is one of the most common dental diseases. Compared with healthy periodontal tissues, the immune microenvironment plays the key role in periodontitis by allowing the invasion of pathogens. It is possible that modulating the immune microenvironment can supplement traditional treatments and may even promote periodontal regeneration by using stem cells, bacteria, etc. New anti-inflammatory therapies can enhance the generation of a viable local immune microenvironment and promote cell homing and tissue formation, thereby achieving higher levels of immune regulation and tissue repair. We screened recent studies to summarize the advances of the immunomodulatory treatments for periodontitis in the aspects of drug therapy, microbial therapy, stem cell therapy, gene therapy and other therapies. In addition, we included the changes of immune cells and cytokines in the immune microenvironment of periodontitis in the section of drug therapy so as to make it clearer how the treatments took effects accordingly. In the future, more research needs to be done to improve immunotherapy methods and understand the risks and long-term efficacy of these methods in periodontitis.